Archaeological researches at "Cañadón de los Mejillones" (south of the Santa Cruz river mouth, Argentina): First results - Franco, Nora Viviana (2010)
The first results of researches carried on south of the mouth of the Santa Cruz river are presented in this paper. They were centered on Cañadón de los Mejillones, Monte Entrance ranch. The most abundant raw material in the area is dacite, which is also the most frequently one used by hunter-gatherers. It was frequently used in an expedient way. However, there is a high frequency of artifacts made on flakes obtained from prepared cores, with centripetal blows from faceted platforms. This technology was dated at ca. 1.224 years BP in a shell midden located south of the canyon mouth, with evidences of utilization of marine and terrestrial resources. Limpets are the most abundant molluscs, suggesting its selection by human populations. The most recent utilization of the canyon was dated at ca. 478 years BP. There are also evidences of utilization of terrestrial and marine resources, with a lower emphasis on molluscs. This could be related to a lower intensity of use of marine resources and a greater emphasis on the terrestrial ones, in a period which is pennecontemporaneus with the contact with european groups, as have been suggested for other spaces within the Patagonian coast.